I. Kant religion and religious upbringing - Šileikaitė, Diana (Acta Paedagogica Vilnensia, 2005)
This article attempts to show how the philosophy of Kant influenced his concept of religious upbringing. The content and methods of religious upbringing are presented that are based on Kant’s approach to morality, God, prayer, the Holy Scripture. Religion for Kant is the tool of moral development, he proposes to introduce children to the most important religious concepts early. Moral catechism must be provided for children prior to the religious catechism. On the one hand, religion without morality for Kant is reprehensible and unacceptable, on the other hand, morality without religion is not complete, so religious upbringing is applicable only after the moral upbringing, i.e. when the pupil already perceives himself as a free being, who is free only due to his will and autonomy, and who is creating universally applicable laws that he himself obeys. If not the inclination to evil in human nature, there would be no need to constantly fight for the purity of the provision, nor would freedom be possible. Religion not only doesn’t hinder progress, as has been written by a number of eighteenth century philosophers, but quite the opposite –an adequate religious education improves children’s honesty, fairness, diligence, kindness and gentleness. This education also fosters tolerance for other religions, because they are merely different forms of expression of the same faith.